Peran Rumah Baca Rumbai Dalam Meningkatkan Literasi Membaca Masyarakat Kota Jambi Tahun 2024 - Nurpadilla, Nurpadilla (Baitul ’Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
Introduction. This study examines the role of the Rumbai Reading House in improving the reading literacy of the people of Jambi City. Established in 2015, the Reading House provides reading materials and literacy activities to support community learning and reading culture. Data Collection Methods. This study employed a descriptive qualitative approach. Data were collected through observations, interviews, and documentation involving the Head of the Reading House, its members, and the community. Data validity was ensured through triangulation. Data Analysis. The collected data were analyzed descriptively to identify the role of the Rumbai Reading House, the supporting and inhibiting factors, and the efforts made to improve community reading literacy. Results and Discussion. The findings show that the Rumbai Reading House serves as a source of information, a learning mediator, and a driver of literacy activities. However, community visits and reading interest remain low. The main obstacles include limited human resources, funding, public awareness, and collections, while its strategic location and available facilities support literacy activities. Conclusion. The Rumbai Reading House has contributed to improving community reading literacy through various literacy programs. Strengthening human resources, expanding collections, increasing funding, and developing attractive literacy programs are recommended to improve community participation.